Biodegradation of polyvinyl chloride plastic films by enriched anaerobic marine consortia. (June 2020) - Giacomucci, Lucia; Raddadi, Noura; Soccio, Michelina; Lotti, Nadia; Fava, Fabio
Abstract: Plastics remarkably contribute to marine litter, which is raising serious concerns. Currently, little is known about the fate of most plastics entering the marine environment and their potential biodegradation rate and extent under anoxic conditions. In this work, biodegradation of polyvinyl chloride (PVC) films by consortia enriched from marine samples (litter and water) was evaluated in anaerobic microcosms. After 7 months, three microcosms showed dense biofilms on plastic surfaces, gravimetric weight losses up to 11.7 ± 0.6%, marked decreases in thermal stability and average molecular weight of the polymer, suggesting microbial attack towards polymer chains. After 24 months, further three consortia showed the same abilities. Microbial communities analyzed at month 24 included taxa closely related to those previously reported as halogenated organic compounds degraders. The study is the first report on PVC biodegradation by marine anaerobic microbes and provides insights on potential biodegradation of the plastic film introduced into the sea by native microbes. Graphical abstract: Image 1 Highlights: Polyvinylchloride (PVC) biodegradation by marine anaerobic consortia assessed. Three incubated films showed thermal stability/mass/Mn% reductions after 7 months. Polymer chains biodegradation demonstrated after 7 months. Hydrocarbon degrading/dechlorinating taxa present in PVC-associated communities.